Perceptual Mapping Warung Makan Upnormal dalam Pasar Warung Makan Kekinian di Purwokerto - Shafrani, Yoiz Shofwa; Sochimin, Sochimin (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The development of the culinary business, especially restaurants/restaurants in Indonesia, can be seen from the increasing number of restaurants in Indonesia. The success of restaurants in attracting consumers is the presence of flavors that can adjust to consumer tastes, strategic locations, quality facilities and services and appropriate prices. In 2017 to 2018 in Purwokerto, starting with the emergence of Warunk Up Normal, then many restaurants with modern nuances emerged that added several supporting facilities. Realizing this, every company must be able to compete to attract consumer interest and first must know the position of its product compared to other restaurant products so that it can make the right strategy. To find out the position of the product, it is necessary to do a perceptual mapping, which is a quantitative analysis tool that can represent the position of the products. Observations on the phenomena that occurred in the six restaurants studied, namely Warunk UpNormal, Dapoer Prambanan, Nyong Kopitiam, #WKWK, Warung Ngapak and Level Up and distributed questionnaires to respondents. Data is analyzed using the multidimensional scaling method which is intended to determine the distribution or position and competition that occurs based on consumer decision-making factors in purchasing. The results showed that the position of the restaurant that experienced competition seen from the consumer decision-making factor was the attribute or price factor and facilities.